Trends and survival benefits of bilateral breast-conserving surgery in patients with metachronous bilateral breast cancer - Qiuyan Huang; Qingzhong Lin; Yinlong Yang (BMC Women's Health)
Abstract Background This study aims to investigate the temporal trends and survival outcomes of bilateral breast-conserving surgery (BCS) in women diagnosed with metachronous bilateral breast cancer (MBBC) in the USA from 2000 to 2019. Methods Patients with stage T0-T3 and stage 0-III MBBC who underwent unilateral BCS on one side and different surgical procedures on the contralateral side from 2000 to 2019 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. The Cochrane-Armitage test for trend was employed to assess the trends in contralateral breast surgical procedures, including BCS, mastectomy (M) and breast-reconstruction (BR). Overall survival (OS) and breast cancer-specific survival (BCSS) were analyzed using Kaplan-Meier curves and univariate and multivariate Cox proportional hazards regression analyses. Since BR is typically performed following M, survival data for the BR and M groups were combined and collectively analyzed as the M group. Results A total of 9571 patients with stage T0-T3 and stage 0-III who underwent unilateral BCS were included in this study, with 75.84% (n = 7,259) opting for BCS treatment. The proportion of BCS was decreased significantly from 90.79% in 2000 to 74.04% in 2019 (P < 0.0001). Older age was positively correlated with BCS, while recent diagnosis, late T stage, lymph node metastasis, invasive lobular carcinoma and chemotherapy were negatively correlated with BCS. Kaplan-Meier survival analysis indicated that BCS patients had better OS (P < 0.001) and BCSS (P < 0.001) compared with patients receiving M. Univariate Cox analysis indicated that BCS showed significant statistical differences in both OS and BCSS. Specifically, the hazard ratio (HR) for OS and BCSS were 0.717 (95% CI 0.649–0.791, P < 0.001) and 0.484 (95% CI 0.422–0.556, P < 0.001), respectively. Multivariate Cox analysis indicated that BCS was not an independent prognostic factor for OS (HR = 1.012, 95% CI 0.904–1.132, P > 0.05), suggesting no significant difference in OS between the BCS and M groups. Conversely, BCS was an independent favorable prognostic factor for BCSS (HR = 0.746, 95% CI 0.634, 0.877; P < 0.05). Conclusion Despite the initial high utilization of BCS in MBBC patients, our study revealed a decline in its usage over the course of the study period. Importantly, this decrease did not impact OS, suggesting the safety of BCS for MBBC patients. In light of these findings, clinicians are encouraged to recommend BCS for eligible MBBC patients, emphasizing its viability as a treatment option.